PENDIDIKAN LINGKUNGAN DALAM PERSPEKTIF ISLAM: INTEGRASI NILAI-NILAI QUR’ANI, ETIKA EKOLOGIS, DAN PERAN PENDIDIKAN ISLAM DALAM KONSERVASI ALAM - Arif Atma Mahendra; Defriyadi; Ali Murtaho; Baharudin; Zulhanan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study explores the concept of environmental education within the framework of Islamic teachings by examining Qur’anic values, prophetic traditions, and the role of Islamic education in strengthening ecological awareness. The research aims to identify core Islamic principles related to environmental preservation such as khalifah (stewardship), amanah (trust), ihsan (excellence), and mizan (balance) and analyze their relevance to modern ecological issues. Using a qualitative library research approach, this study reviews classical and contemporary Islamic literature, as well as scholarly works on eco-Islam and environmental ethics. The findings reveal that Islam provides a comprehensive environmental worldview that emphasizes the responsibility of humans as guardians of the earth, prohibits destructive actions, and encourages sustainable use of natural resources. Furthermore, Islamic education, both formal and non-formal, plays a strategic role in integrating ecological values into learning activities and daily life practices. This study concludes that Islamic environmental education is essential for shaping environmentally conscious behavior and can contribute to the development of sustainable ecological ethics in contemporary society.